Fridericus Sohnerus Heilbrunnensis Gedani Ad S. Barbarae Verbi Divini Minister. Natus MDCXV. Denatus MDCLXXXVII. / Carol de la Haye. - La Haye, Charles de (1641-nie przed 1707) (1687)
Przedstawia portret w popiersiu Friedricha Söhnera (1615-1687).